Ответы и объяснения

2013-08-08T19:53:55+00:00
1)  \frac{3x-2}{x-1} + \frac{x-4}{x+3} = \frac{3(5x-1)}{(x-3)(x+3)} 

 \frac{3x-2}{x-1} = \frac{15x-3}{(x-3)(x+3)} - \frac{x-4}{x+3} 

 \frac{3x-2}{x-1} = \frac{15x-3-(x-4)(x-3)}{ x^{2} -9}
отсюда 
 \frac{3x-2}{x-1} = \frac{- x^{2} +22x-15}{ x^{2} -9}  x\neq 1; x \neq -3;x \neq 3
(2-3x)( x^{2} -9)=(x-1)( x^{2} -22x+15)
-3 x^{3} +2 x^{2} +27x-18= x^{3} -23 x^{2} +37x-15
4 x^{3} -25 x^{2} +10x+3=0
корни находи сама.
2)(2 x^{2} +2)(4 x^{2} -1)-(4 x^{3}-13)(2x-1)=(2x-1)(4 x^{2} -1)
4x^3+6x^2+26x-15=8x^3-4x^2-2x+1
2x^3-5x^2-14x+8=0
Корни по схеме горнера и по теореме виетта находи
x=-2; x= \frac{1}{2} ; x=4
Пожалуста=3